2022
DOI: 10.17582/journal.pjar/2022/35.1.36.46
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Local and Multinational Maize Hybrids for Tolerance Against High Temperature using Stress Tolerance Indices

Abstract: The current study was conducted to evaluate maize hybrids for their high temperature tolerance ability based on their performance as assessed through different high temperature stress indices. Nine maize hybrids were screened under optimal and high temperature stress conditions (late sowing) for three consecutive spring seasons (Spring 2017(Spring -18, 2018(Spring -19 and 2019, laid out under split-split-plot design under RCBD. Results reveled significant differences among stress indices for all three season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(29 reference statements)
1
1
0
Order By: Relevance
“…Among maize hybrids, YH-5482 and YH-5395 out-performed other hybrids under water stress conditions while JPL-1908 and NK-8441 were proved to be fairly drought susceptible hybrids based on their agro-morphological traits. These hybrids (YH-5482 and YH-5395) were also proved as heat tolerant hybrids in the previous studies ( Rahman et al, 2022 ). Therefore, these hybrids could be distributed in large quantities to the farming communities in drought prone areas to improve their livelihood.…”
Section: Discussionsupporting
confidence: 60%
“…Among maize hybrids, YH-5482 and YH-5395 out-performed other hybrids under water stress conditions while JPL-1908 and NK-8441 were proved to be fairly drought susceptible hybrids based on their agro-morphological traits. These hybrids (YH-5482 and YH-5395) were also proved as heat tolerant hybrids in the previous studies ( Rahman et al, 2022 ). Therefore, these hybrids could be distributed in large quantities to the farming communities in drought prone areas to improve their livelihood.…”
Section: Discussionsupporting
confidence: 60%
“…Several researchers also showed that variations among cotton genotypes for key agronomic traits will provide a strong base to run a breeding program to improve an existing genotype or to develop a new cotton variety Aslam et al, 2022;Hussain et al, 2023a;Manan et al, 2022;Munir et al, 2020;Rahman et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The correlation coefficient analysis was used to establish the relationship between studied plant traits in cotton genotypes under heat stress conditions. Plant scientist is widely using this statistical to conclude based on associations between plant traits in several crop species under different climatic conditions (Mumtaz et al, 2018;Yousaf et al 2021a;Yousaf et al, 2021b;Riaz et al;Rahman et al, 2022). The results revealed the presence of a positive correlation of seed cotton yield with plant height, plant population per hectare, bolls per plant, sympodial branches per plant and nodes per plant.…”
Section: Correlation Coefficient Analysismentioning
confidence: 99%